Habituation facilitates host-inquiline cohabitation in termites - Martins, Elisa Gabriella (2021)
Termite nests offer an environment with favorable conditions for several invertebrate species and, among them, other termites known as inquilines. However, the biological mechanisms surrounding this cohabitation remain unveiled. Termites, like other social insects, are able to distinguish nestmates from non-nestmates, being aggressive towards non-nestmates. A mechanism that can reduce aggression is habituation. Habituation is a physiological mechanism by which animals or cells become less reactive to a frequently repeated stimulus. Here we tested the hypothesis that habituation attenuate host-inquiline lethal interactions, favoring cohabitation. To test this hypothesis, we experimentally exposed the nest builder Cornitermes cumulans termites to their inquiline Curvitermes odontognathus in assays where host and inquilines were kept apart but shared headspace, prior to being let to establish physical contact to each other. We found that as the prior exposition time increased the duration of lethal interactions between hosts and inquilines decreased. This result could not be attributed to indi- vidual exhaustion, as both inquilines and hosts survived longer in longer treatments, as opposed to individuals in shorter treatments. We also found that the duration of resting increased with the prior heterospeciﬁc exposure time. This suggests that the hosts reduced patrolling activities, possibly because they were already familiar with the inquilines. This result suggests that habituation facilitates cohabitation in termites, lowering the intensity of host-inquiline lethal interactions. Keywords: Inquilinism · Hosts · Habituation